Pasireotide for Refractory Hypoglycemia in Malignant Insulinoma- Case Report and Review of the Literature - Oziel-Taieb, Sandrine; Maniry-Quellier, Jemima; Chanez, Brice; Poizat, Flora; Ewald, Jacques; Niccoli, Patricia (Frontiers in Endocrinology, 2022)
Malignant insulinomas are functional neuroendocrine tumors of the pancreas and the primary cause of tumor-related hypoglycemia. Malignant insulinoma is rare and has a poor prognosis. We report a case of malignant insulinoma with metastases in the liver and lymph nodes in a 64-year-old patient with severe and refractory hypoglycemia. After several ineffective locoregional and systemic lines of treatment for the secretory disease, the introduction of pasireotide –a second-generation somatostatin analog— provided an improved clinical and secretory evolution both quickly and sustainably, with an excellent safety profile and antitumor efficacy. Pasireotide is an effective and well-tolerated therapy in the treatment of refractory hypoglycemia in metastatic insulinoma.